1986
DOI: 10.1111/j.1445-2197.1986.tb07095.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventable Causes of Death and Disability From Neurotrauma

Abstract: Preventable causes of death and disability have been studied retrospectively in a series of 1161 cases of neurotrauma occurring in New South Wales in 1977–78, and prospectively in 153 cases of neurotrauma occurring in country districts in South Australia in 1981–82. In the first study, it was found that at least 80 deaths could be attributed to preventable causes; chiefly, transfer to an inappropriate hospital and/or delay in instituting treatment. Apparent failures in initial management of shock and airway ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Monocytes are constantly egressing from the bone marrow and stay in circulation for an average of 3 days before they egress into tissues to become long-lived tissue macrophages (58, 59). Our previous studies using the MΦ-QVOA in the dual-inoculated SIV-infected pigtailed macaque model have demonstrated that monocytes harbor replication-competent SIV and produce virus when allowed to mature to macrophages in culture (4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocytes are constantly egressing from the bone marrow and stay in circulation for an average of 3 days before they egress into tissues to become long-lived tissue macrophages (58, 59). Our previous studies using the MΦ-QVOA in the dual-inoculated SIV-infected pigtailed macaque model have demonstrated that monocytes harbor replication-competent SIV and produce virus when allowed to mature to macrophages in culture (4).…”
Section: Resultsmentioning
confidence: 99%
“…In tissue, long-lived macrophages are made up of both monocytes that traffic into tissues and differentiate into monocyte-derived macrophages and resident tissue macrophages that are derived from embryonic progenitors (58, 59, 62). The embryonal macrophages are long-lived and self-replenish, while the half-life of MDMs varies from a few days up to several months, and the MDMs are reseeded by the blood (59).…”
Section: Resultsmentioning
confidence: 99%
“…With respect to trauma patients, in particular those with head injury, the prevention of secondary injury by effective airway management and treatment of hypotension with fluid resuscitation and drug therapy has been clearly demonstrated 18–21 . In spite of the increasing ability to institute these measures across all hospital types as a result of educational programs such as the Early Management of Severe Trauma (EMST), our data indicates that skilled care is not universally available.…”
Section: Discussionmentioning
confidence: 85%
“…A New South Wales study in 1977 involving 1161 neurotrauma cases [5] found that 41% of neurotrauma cases spent more than 2 hours on the way to hospital. One hundred ten cases suffered delays because of a lack of modern transport facilities.…”
Section: Epidemiologymentioning
confidence: 99%
“…Between the years 1925 and 1970 road traffic authorities and public health bodies paid little attention to the escalating mortality and morbidity rates resulting from road, industrial, farming, and sporting accidents. However, during the decades of the 60s and 70s, convincing data were produced by surgeons and pathologists [1][2][3][4][5]. The National Road Trauma Committee of the Royal Australasian College of Surgeons became the catalyst and with the support of the media, insurance companies, and, later, federal and state legislators, a dramatic reduction in traffic accidents and neurotrauma occurred.…”
mentioning
confidence: 99%